PENGARUH MANAJEMEN LABA DAN UKURAN PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2013-2017 - yulius gessong sampeallo; Fariyanti Fariyanti; Jeri Jeri (Politeknik Negeri Samarinda, 2020)
This research's purpose was to find out the influence of earnings management meansured and company size to CSR (Corporate Social Responsibility) in manufac-turing companies listed on the Indonesia Stock Exchange in the period 2013-2017 as measured by discretionary accruals. This type of research is an empirical study. The research was conducted on 7 manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017 and company financial reports on the Indonesian Stock Exchange (IDX) web. Data types are quantitative data and secondary data sources and documentation data collection techniques. In a test using the multiple linear regression. The results showed that earnings management had a significant effect on Corporate Social Responsibility (CSR) in mining sector companies listed on the Indonesia Stock Exchange in the period 2013-2017 but not significant with a sig value of 0.292 above the significance (α = 0, 05) and the size of the company has a significant effect on Corporate Social Responsibility in manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2017 with a significant value of 0.022 or below the level of significance (α = 0.05). Keyword: Profit management, CSR, Manufacturing company